2011
DOI: 10.5204/intjfyhe.v2i2.89
|View full text |Cite
|
Sign up to set email alerts
|

The significance of being first: A consideration of cultural capital in relation to “first in family” student’s choices of university and program. A Practice Report

Abstract: This presentation explored the differences between expectations of first in family students and students who have immediate family members (parents, care givers, or siblings) who have attended university before them. The authors draw on Bourdieu's notion of cultural capital to examine how being first in family influences student expectations. Data from a large survey of over 3,000 first year students conducted in 2010 across the three South Australian universities is used to explore the demographic make-up of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 13 publications
1
17
0
Order By: Relevance
“…Ninety-seven (46.0%) students were non-FIF. These figures are similar to previous research at Australian universities (Luzeckyj et al, 2011).…”
Section: Resultssupporting
confidence: 81%
See 3 more Smart Citations
“…Ninety-seven (46.0%) students were non-FIF. These figures are similar to previous research at Australian universities (Luzeckyj et al, 2011).…”
Section: Resultssupporting
confidence: 81%
“…FIF students knew significantly fewer people who had attended university than non-FIF. In their Australian study, Luzeckyj et al (2011) found that FIF students based their expectations of university on sources removed from their familial and friendship networks, while non-FIF students were informed by these networks. Recent research in the US indicates that firstgeneration students exhibit greater confusion regarding expectations related to academic workload and assessment (Collier & Morgan, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Bathmaker et al (2013) found that working-class students in their UK study required much consideration and planning to decide on HE, while most middle-class students considered enrolment the norm. A study of over 3000 commencing students at three South Australian universities found that FIF students made the decision to enrol later in school or life than non-FIF students (Luzeckyj, King, Scutter, & Brinkworth, 2011).…”
Section: Impact Of Schooling and Sesmentioning
confidence: 99%